Between Worlds in Shakespeare's Comedy of Errors. (3rd April 2021) - Degenhardt, Jane Hwang; Turner, Henry S.
ABSTRACT: This article turns to Shakespeare's Comedy of Errors (1594) in order to revise critical accounts of globalization and to propose a contrasting notion of "world" as a function of affective experience, collective narration, and virtual witnessing. Shakespeare's play captures how a newly global imaginary was beginning to disrupt many of the foundations of personal identity and the familiar reference points of the worlds that sustained it. The Comedy of Errors acknowledges the integrative effects of a globalizing system while also emphasizing its multiply-centered, regional specificity; Shakespeare models not a single, totalizing globality but a plurality of worlds characterized by continuous rupture, reconfiguration, and an ongoing state of in-betweenness. Not only does the play illuminate a non-Eurocentric view of globalization but it explores the alienation that attends migration and displacement at a global scale and the ways these movements mark the body for violence and refigure the human relationships that bond people together. In doing so, the play reveals an experience of exclusion that is constitutive of race insofar as its somatic determinations follow a logic that is both incomprehensible and absolute. The play also demonstrates how dramatic processes of collective story-telling and mutual witnessing can re-world both subject and community alike, showing us how "globalization" is an historically-contingent iteration of "worlding" that is neither static, inevitable, nor permanent.